2016
DOI: 10.4103/1817-1745.193374
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and magnetic resonance imaging evaluation of pediatric spinal anomalies

Abstract: Context:Spinal dysraphisms are congenital abnormalities of the spine due to imperfect fusion of midline mesenchymal, bony and neural structures. Imaging plays a vital role in their evaluation as significant portion of patients may present with concurrent anomalies that need to be corrected simultaneously to avoid repeat surgeries.Aims:The aims of the study were to evaluate Spinal dysraphisms using USG and MRI and to correlate imaging findings with operative findings in patients undergoing surgery.Settings and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 14 publications
5
14
0
3
Order By: Relevance
“…We shared comparable results with Dhingani et al who found that the lumbosacral spine was the most commonly involved spinal segment found in 52.63% of patients, followed by sacrococcygeal region (34.21%) [17].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We shared comparable results with Dhingani et al who found that the lumbosacral spine was the most commonly involved spinal segment found in 52.63% of patients, followed by sacrococcygeal region (34.21%) [17].…”
Section: Discussionsupporting
confidence: 91%
“…Our study results as regards spinal ultrasound are comparable with study by Dhingani et al which showed that the most common anomaly was tethered cord seen in 23 (79.31%) patients, syrinx (62.06%), MMC (48.27%), and lipomyelomeningeocele (27.58%) [17]. And another study by Taahira Nishtar et al, which revealed that 2 of the studied 53 patients (4%) has diastematomyelia [18].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations